Effectiveness of the Tier 1 Program of Project P.A.T.H.S.: Findings Based on Three Years of Program Implementation - Daniel T. L. Shek; Rachel C. F. Sun (The Scientific World Journal)
The Tier 1 Program of the Project P.A.T.H.S. (Positive Adolescent Training through Holistic Social Programmes) is a positive youth development program implemented in school settings, utilizing a curricular-based approach. In the third year of the Full Implementation Phase, 19 experimental schools (n = 3,170 students) and 24 control schools (n = 3,808 students) participated in a randomized group trial. Utilizing the six-wave longitudinal data, ANCOVA, and linear mixed models controlling for differences between the two groups in terms of Wave 1 pretest scores, personal variables, and random effects of schools, it was revealed that participants in the experimental schools showed significantly better development than did participants in the control schools at post-test (Wave 6) based on different indicators of positive youth development derived from the Chinese Positive Youth Development Scale and other measures. Students in the experimental schools also displayed a lower level of intention to engage in problem behavior and better school adjustment than did students in the control schools. Similarly, differences between experimental participants who perceived the program to be beneficial and control participants were found.